Music Advertising People: علي عبد الله (Al-Academy, 2015)
Songs hawkers or steadfast in the market of the most important sources of musical heritage, most notably the popular influence in people's lives and their careers cultural, as history records for Those tunes Chorales and invested by the vendors to attract these people in order to promote their goods and for marketing.This study reviews a brief history of those tunes drafted by the innate taste stems from folk music with the rhythms of vigor and vitality originated and grew up on the audio format is consistent with the need for people eager to hear the tunes left moved the feelings and send to communicate with the idea that came from her.As contemplated in the study models of those melodies and recording musician with the installation of rhythms and the method of presentation within the concept of time and space imposed by the nature of performance , whether they are fixed within the limits of the conventional market , or moving on the streets and roads and alleys of cities .And concludes the study to identify the composers of the Worlds and local composers who have benefited from those melodies and dealt in musical compositions and lyrics that have become part of the musical heritage of the people who represent a particular country or region is referred to by the identity of the melody and the popular connotations